HUBUNGAN STATUS SOSIAL DAN PERISTIWA TUTUR ANTARA APARAT DESA DAN MASYARAKAT - Safitri Djafar (TELAGA BAHASA, 2020)
The purpose of this research is to describe the social status, speech events, and relation between the social status and the speech events between village officers and the society in Kantor Desa Lonuo, KecamatanTilongkabila, KabupatenBone Bolango, viewed from the economic, educational, and employment levels. The method used is the qualitative method and the type of research is descriptive research. The data in this study were the utterances spoken by village officers and the society in DesaLonuo. The data sources were obtained from the village officers and the society in Lonuo. The results showed : (1) the social status of the society in Lonuo was seen from the economic level, it was below the average and the public education only reached the level of primary school (2) speech events occur between the sub-district officers, the village officers, and the society in a meeting activities, or in meeting coordination of farmer groups, and between the society and kepala dusun II in the making of a poverty statement, and (3) the relation between social status and speech events is very close, and this speech event shows differences in the use of language that had been seen from social status at the level of education of each speaker.